2020
DOI: 10.3390/life10110304
|View full text |Cite
|
Sign up to set email alerts
|

Human Mitochondrial Pathologies of the Respiratory Chain and ATP Synthase: Contributions from Studies of Saccharomyces cerevisiae

Abstract: The ease with which the unicellular yeast Saccharomyces cerevisiae can be manipulated genetically and biochemically has established this organism as a good model for the study of human mitochondrial diseases. The combined use of biochemical and molecular genetic tools has been instrumental in elucidating the functions of numerous yeast nuclear gene products with human homologs that affect a large number of metabolic and biological processes, including those housed in mitochondria. These include structural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 304 publications
(332 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, we also demonstrated that GATA-1s over-expression was accompanied by markedly increased levels of SDHC, a subunit of the respiratory chain SQR complex, without any appreciable change in the other three subunits (SDHA, SDHB, SDHD) of the SQR tetramer [6]. In this regard, it is to be noted that, although it has long been assumed that mitochondrial ROS can only be produced at complexes I and III, more recent data pointed out that complex II has a role in ROS production, thus significantly contributing to the mitochondrial control of apoptosis and cell proliferation [12,13,[15][16][17]. In this context, a growing body of research has focused on the role of SDH as a tumor suppressor factor and the relationship between complex II dysregulation and tumorigenesis consequent to chronic ROS elevation and impaired regulation of apoptosis [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we also demonstrated that GATA-1s over-expression was accompanied by markedly increased levels of SDHC, a subunit of the respiratory chain SQR complex, without any appreciable change in the other three subunits (SDHA, SDHB, SDHD) of the SQR tetramer [6]. In this regard, it is to be noted that, although it has long been assumed that mitochondrial ROS can only be produced at complexes I and III, more recent data pointed out that complex II has a role in ROS production, thus significantly contributing to the mitochondrial control of apoptosis and cell proliferation [12,13,[15][16][17]. In this context, a growing body of research has focused on the role of SDH as a tumor suppressor factor and the relationship between complex II dysregulation and tumorigenesis consequent to chronic ROS elevation and impaired regulation of apoptosis [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the main source of intracellular reactive oxygen species (ROS) that are mainly generated at complex I and at complex III of the respiratory chain (RC). The primary ROS produced in mitochondria is superoxide anion (O 2 − ) that can be rapidly converted to hydrogen peroxide by superoxide dismutase (SOD) [12,13]. Notably, although previously largely neglected, more recent data points to a relevant role of complex II, the succinate dehydrogenase (SDH) or succinate-ubiquinone oxidoreductase (SQR) as a key redox regulator of ROS production [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when glucose concentration is very low or when yeast cells grow on non-fermentable carbon sources, energy is produced by respiratory metabolism. Based on these characteristics, yeast is a powerful platform for gaining better understanding of the underlying molecular basis of human diseases [67]. In fact, although human mitochondria are more complex, the high similarity between yeast and human mitochondrial biogenesis and function renders Saccharomyces cerevisiae an excellent model for studying human mitochondrial physiopathology.…”
Section: Mitochondrial Carriers and Oxphosmentioning
confidence: 99%
“…It is therefore possible to distinguish genetic defects caused by (i) alterations in mitochondrial DNA (mtDNA), ∼15%, e.g., Neuropathy, Ataxia, Retinitis Pigmentosa (NARP), Maternally Inherited Leigh's Syndrome (MILS) and Leber's Hereditary Optic Neuropathy (LHON) [5] and (ii) nuclear DNA (nDNA) mutations, which are inherited as Mendelian disorders. A recent review provided an update on the contribution of nuclear genes that impair mitochondrial respiration in patients and have been characterized in yeast [6]. More than 150 distinct genetic mitochondrial dysfunction syndromes characterized by a diminished OXPHOS capacity have been described [5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%